A new species of Chama (Bivalvia, Chamidae) from Mexico - Valentich-Scott, Paul; Coan, Eugene V. (Zootaxa, 2010)
While preparing a review of the bivalve mollusk fauna of the Panamic Province, we encountered a conspicuous, colorful species of the genus Chama Linnaeus, 1758, that could not be identified with any named species. After examining type specimens at The Natural History Museum, London (BMNH), the United States National Museum of Natural History (USNM), the Academy of Natural Sciences, Philadelphia (ANSP), the California Academy of Sciences (CAS), the Natural History Museum of Los Angeles County (LACM), and the Santa Barbara Museum of Natural History (SBMNH), we have concluded that this species is new to science.